(untitled) (Research, Society and Development, 2020)
The pregnancy-puerperal cycle is a moment integrated by major transformations both physical, psychic and emotional, being a very important experience for women, the couple and also the family. The objective was to identify, analyze and characterize in the literature studies addressing the theme: Women in the puerperium and the prevention of pathologies linked to maternal and child morbidity and mortality. This is an integrative review, carried out from February to September 2020. Inclusion criteria were considered: articles that presented the full text, in Portuguese and English, published in the last five years, and that addressed the theme in question. The following were excluded from the research: incomplete works, theses, dissertations and those who did not contemplate the teme. For data collection, the Virtual Health Library – VHL, on the following bases: Nursing Database, and Latin American and Caribbean Health Sciences Literature. The descriptors used were: Puerperium. Morbidity and mortality. Maternal Mortality. Mortality Neonatal. Nursing care. The studies were grouped into two categories, according to their similarity: maternal and child mortality and associated factors and puerperal nursing care in primary health care and at home. In conclusion, it was found that the mother’s health in the puerperium has repercussions on the child’s health, emphasizing how essential the nurse’s attention and assistance in the puerperium has become, given the fears, doubts and difficulties that may arise after hospital discharge. From this, the puerperal home visit acquired paramount importance, since it allows to identify any risks that the triad mother, child and family may present.